Charge transport in functionalized multi-wall carbon nanotube-Nafion composite - Sangeeth, C. S. Suchand; Kannan, Ramaiyan; Pillai, Vijayamohanan K.; Menon, Reghu (Journal of Applied Physics, 2012)
The charge transport in sulfonated multi-wall carbon nanotube (sMWNT)-Nafion composite is reported. The scanning electron microscope images of the composite, at 1 and 10 wt % of sMWNT, show that the nanotubes are well dispersed in polymer matrix, with conductivity values of 0.005 and 3.2 S/cm, respectively; and the percolation threshold is nearly 0.42 wt. %. The exponent (similar to 0.25) of the temperature dependence of conductivity in both samples indicates Mott's variable range hopping (VRH) transport. The conductance in 1 wt. % sample increases by three orders of magnitude at high electric-fields, consistent with VRH model. The negative magnetoresistance in 10 wt. % sample is attributed to the forward interference scattering mechanism in VRH transport. The ac conductance in 1 wt. % sample is expressed by sigma(omega) proportional to omega(s), and the temperature dependence of s follows the correlated barrier hopping model. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4749264]